Effects of gamification on EFL learning: a quasi-experimental study of reading proficiency and language enjoyment among Chinese undergraduates - Cheng, Jing; Lu, Chen; Xiao, Qiaoling (Frontiers in Psychology, 2025)
BackgroundIn foreign language education, educators struggle with declining student engagement as traditional EFL teaching, relying on passive lectures and dull materials, hampers proficiency and dampens passion. Gamification has emerged as a potential solution. This quasi-experimental study, based on the broaden-and-build theory, examined the effects of gamification on reading proficiency and foreign language learning enjoyment (FLLE) among Chinese undergraduates studying English as a foreign language (EFL).MethodsData were collected from 220 first-year undergraduates at a Chinese university through reading assessments and the Chinese Foreign Language Enjoyment Scale, supplemented by interviews with nine participants picked from the first-year undergraduates.ResultsThe findings revealed a significant increase in gamification's benefits for EFL reading proficiency. FLLE's private dimension, tied to personal enjoyment, was crucial. Additionally, gamified settings improved focus, teamwork, and communication.DiscussionThis study supports integrating gamification to boost engagement and outcomes. However, the study was limited to a specific context and duration. Therefore, future studies should identify key gamification elements and their long-term impact.